CREATIVITY AND WORLD FAMOUS DESIGNERS IN THE DESIGN AND CREATION OF DRESSES (American Journal of Interdisciplinary Research and Development, 2022)
Today, clothes are most often produced for the mass consumer, and in this case, a fashion designer prepares industrial collections. These are high-quality ready-made clothes that were invented and created in the workshops of famous fashion designers. There are also unique collections called "haute couture": fashion designers create design projects implemented for the elite, for those who are able to afford to dress in the most fashionable, stylish and high-quality ensembles created on the basis of the projects of brilliant creators. In this article, we can discuss about creativity and world famous designers in the design and creation of dresses.